Challenges and Potential of Local Television in Cuba for Managing Community Cultural Developmentr the management of community cultural development (Islas, 2025)
Introduction: Considering the reach of local media in social transformation, this article analyzes the challenges and potential of local television in managing community cultural development within the Cuban context.Methods: To determine and analyze the dimensions of the analytical category used, grounded theory is adopted as the main research method, along with the metasynthesis of qualitative studies as a source of empirical data, supplemented by semi-structured interviews with experts.Results: The main strengths of local television in Cuba lie in its cultural proximity to its audiences through content that prioritizes local realities and highlights local practices and identities. The primary challenges involve its consolidation as a platform for participatory social dialogue and social transformation.Conclusions: To make a more significant contribution, local television in Cuba must facilitate and be part of formative processes that strengthen communication skills and competencies for citizen participation in the public sphere.
Keywords: community communication; community cultural development; local media; local television in Cuba; community media